Interpretasi Lirik Lagu “Pilu Membiru”, “Rehat”, “Sulung”, dan “Saudade” Karya Kunto Aji dalam Album Mantra-Mantra Sebuah Kajian Semiotika Riffaterre - Intan Tri Retnowati; Moh. Muzakka; Laura Andri Retno Martini (Wicara: Jurnal Sastra, Bahasa, dan Budaya, 2022)
AbstractThe purposes of this study are to describe heuristic and hermeneutic reading, matrices and model, hypogram, and indirect expression of the lyrics of the songs “Pilu Membiru”, “Rehat”, “Sulung”, dan “Saudade” by Kunto Aji in the Mantra-Mantra albums. This study uses descriptive method. The data was collected using listening and note-taking technique. The result of this study show that (1) the heuristic and hermeneutic reading, (2) matrices and model, (3) hypogram actual and potential, and (4) indirect expression of the lyrics of the songs “Pilu Membiru”, “Rehat”, “Sulung”, dan “Saudade” by Kunto Aji in the Mantra-Mantra albums using Riffaterre’s semiotic theory.Keywords: song lyrics, Riffaterre semiotic, Mantra-Mantra, Kunto Aji, hypogram AbstrakPenelitian ini bertujuan untuk mendeskripsikan pembacaan heuristik dan hermeneutik, matriks dan model, hipogram, dan ketidaklangsungan ekspresi dari lirik lagu “Pilu Membiru”, “Rehat”, “Sulung”, dan “Saudade” karya Kunto Aji dalam album Mantra-Mantra. Penelitian ini menggunakan metode deskriptif.  Pengumpulan data dilakukan dengan menggunakan teknik menyimak dan mencatat. Hasil penelitian menunjukkan (1) pembacaan heuristik dan hermeneutik, (2) matriks dan model, (3) hipogram aktual dan potensial, dan (4) ketidaklangsungan ekspresi dari lirik lagu “Pilu Membiru”, “Rehat”, “Sulung”, dan “Saudade” karya Kunto Aji dalam album Mantra-Mantra yang menggunakan teori semiotika Riffaterre.Kata kunci: lirik lagu, semiotika Riffaterre, Mantra-Mantra, Kunto Aji, hipogram